2009
DOI: 10.1890/09-0415.1
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient enrichment homogenizes lake benthic assemblages at local and regional scales

Abstract: The compositional heterogeneity of biotic assemblages among sites, or beta-diversity, regulates the relationship between local and regional species diversity across scales. Recent work has suggested that increased harshness of environmental conditions tends to reduce beta-diversity by decreasing the importance of stochastic processes in structuring assemblages. We investigated the effect of nutrient enrichment on the compositional heterogeneity of lake benthic invertebrate assemblages in Ireland at both local … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
154
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 169 publications
(166 citation statements)
references
References 60 publications
8
154
3
1
Order By: Relevance
“…Pioneering work on the effect of drought on the assembly of macro-organisms in pond ecosystems (Chase, 2007) demonstrated that increasing the strength of environmental selection increases the reproducibility of the final community structure; this conclusion is supported by other studies of a variety of natural environments (Donohue et al, 2009;Lepori and Malmqvist, 2009;Helmus et al, 2010;Myers and Harms, 2011), as well as by microcosm studies of eukaryotic microbial (protist) community assembly (Weatherby et al, 1998;Jiang and Patel, 2008). However, it is unclear whether these principles also apply to complex natural microbial communities.…”
Section: Introductionmentioning
confidence: 88%
“…Pioneering work on the effect of drought on the assembly of macro-organisms in pond ecosystems (Chase, 2007) demonstrated that increasing the strength of environmental selection increases the reproducibility of the final community structure; this conclusion is supported by other studies of a variety of natural environments (Donohue et al, 2009;Lepori and Malmqvist, 2009;Helmus et al, 2010;Myers and Harms, 2011), as well as by microcosm studies of eukaryotic microbial (protist) community assembly (Weatherby et al, 1998;Jiang and Patel, 2008). However, it is unclear whether these principles also apply to complex natural microbial communities.…”
Section: Introductionmentioning
confidence: 88%
“…In freshwater ecosystems, nutrient loading by humans not only alters patterns of nutrient cycling (23,24), but can also threaten population persistence (25) and disrupt ongoing species divergence by changing selection regimes (26). Furthermore, nutrient loading can increase parasite prevalence and change evolutionary trajectories of host-parasite interactions (27)(28)(29).…”
mentioning
confidence: 99%
“…Increased levels of eutrophication are often accompanied by a decline in macroinvertebrate diversity (Donohue et al 2009), an increase in density, and a decrease in wet biomass (mollusks with shells) (Crowns et al 1992, Wollheim and Lovvorn 1995, Gong and Xie 2001, Xiong et al 2003. However, most previous research has been restricted to local-scale studies, i.e., in a single lake or in a few lakes (Saether 1980, Kerovec et al 1989, Gong et al 2000, Xiong et al 2003, Timm et al 2006, and few studies have covered a complete range of nutrient concentrations (Brauns et al 2007a, Donohue et al 2009). …”
mentioning
confidence: 99%